FINANCIAL CONTAGION AND INTERDEPENDENCE BETWEEN LATIN AMERICAN AND UNITED STATES MARKETS - Marschner, Paulo Fernando; Ceretta, Paulo Sergio; Souza, Adriano Mendonça; de Lima, Leonardo Gress (Advances in Scientific and Applied Accounting, 2021)
Objective: the objective is to analyze the existence and magnitude of financial contagion and interdependencies between the stock markets of Latin America (Argentina, Brazil, Chile, Mexico and Peru) and the United States. Method: vector autoregressive models (VAR) were applied to the historical series of stock markets index returns in three periods: pre-crisis, crisis and post-crisis. Results: after estimating, it was observed that in the three sample subperiods (pre-crisis, crisis and post-crisis) vector models were adjusted with different lag levels, VAR(1), VAR(3) and VAR(1 ), respectively, showing that in the crisis period the endogenous variables affect the system of simultaneous equations for up to three lag periods, and in the other subsamples for only one period. The main results showed that: i) the pre-financial crisis period is characterized by insignificant levels of interdependence between the Latin American and U.S. markets; ii) during the crisis period, the American market had the power to explain the variance of most Latin American markets; and iii) after the crisis, the ties between the markets in that region and the American market remained in place, but to a lesser extent. Contributions: the evidence found in this research expands the literature and presents new evidence on the relationship between the markets of Latin America and the U.S. The role of the American market on some markets in that region during the crisis, as well as the post-crisis relations, were not fully elucidated by the previous literature.